Associations between snowboard coaches teaching interaction, motion guidance, and effectiveness assessment competencies and learners intentions to continue lessons - Liu, J.; Hu, T.; Yin, J. (Frontiers in Psychology, 2025)
Background: The rise in winter sports following the 2022 Beijing Winter Olympics has led to a surge in snowboarding enthusiasts. However, domestic snowboard coach training remains at a rudimentary stage, resulting in substandard instructor competencies that create negative customer experiences and seriously impede the development of China's snowboarding industry.